Observation on the effect of combined surgery in cataract patients with pterygium - Kshama Dwivedi (Press of International Journal of Ophthalmology (IJO PRESS), 2021)
AIM:To observe the effect of combined surgery in cataract patients with pterygium.METHODS:A prospective single centered study was performed on 22 patients(mean age: 59.05±8.70 years)of concurrent cataract and pterygium(size 2-5 mm in length), who attended the outpatient department during the study period of one year, and the minimum follow up was 3mo-1a for all patients. Mean keratometry(Kmean), mean astigmatism, best corrected visual acuity(LogMAR), preoperatively and 3mo postoperatively had been determined. The corneal curvature, pterygium size and the prediction error(PE)were observed.RESULTS: The amount of PE was <±0.50 D in 18 patients(81.8%)and ±0.50 D to ±1.00 D in 4 patients(18.2%). None of the patients had PE of >1.00 D. The mean axial length did not change significantly(P=0.77)postoperatively. The mean keratometric reading increased from 42.994±1.536 preoperatively to 43.324±1.479 postoperatively but this was not significant(P=0.105). The corneal astigmatism decreased significantly from 2.09±0.789 D preoperatively to 0.523±0.277 D postoperatively(P<0.05). BCVA(LogMAR)significantly improved from 1.007±0.402 preoperatively to 0.024±0.062 postoperatively(P<0.05). No correlation was found between changes in keratometry and PE(r=-0.29, P=0.19). And, there was no correlation was found between pterygium size and PE(r=0.2997, P=0.17). CONCLUSION: Combined phacoemulsification+foldable intraocular lens(IOL)implantation and conjuctival autograft(CAG)application was safe and effective procedure.